2018
DOI: 10.1262/jrd.2018-040
|View full text |Cite
|
Sign up to set email alerts
|

Risk of chromosomal aberration in spermatozoa during intracytoplasmic sperm injection

Abstract: Intracytoplasmic sperm injection (ICSI) has become critical for the treatment of severe male infertility. The principal feature of ICSI is the direct injection of spermatozoon into an oocyte, which facilitates the production of fertilized embryos regardless of semen characteristics, such as sperm concentration and motility. However, the chromosomal integrity of ICSI zygotes is degraded compared to that of zygotes obtained via in vitro fertilization. This chromosomal damage may occur due to the injection of non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…In addition to efficacy there are safety concerns. Despite its widespread application, ICSI has not been subjected to ethical review, animal studies or rigorous testing in humans to assess biological impact and overall safety 20 . The procedure bypasses natural selection safeguards, which may affect offspring and future generations [21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to efficacy there are safety concerns. Despite its widespread application, ICSI has not been subjected to ethical review, animal studies or rigorous testing in humans to assess biological impact and overall safety 20 . The procedure bypasses natural selection safeguards, which may affect offspring and future generations [21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…Chromosomal damage may occur due to the injection of non-capacitated, acrosome intact spermatozoa, which with natural fertilization would never enter the oocytes. Furthermore, it is possible that incubation and pre-treatment of spermatozoa during ICSI results in DNA damage 20 . Some studies have demonstrated an increase in genetic abnormalities, birth defects and developmental delay with the use of ICSI [22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found that there was an increased incidence of aneuploidies, mainly sex chromosome aberrations, among children conceived by ICSI (2). Subfertile men are considered to have higher rates of aneuploid offsprings, secondary to gametes with higher rates of chromosomal segregation errors (3). The invasive nature of the ICSI procedure may also lead to embryonic aneuploidy by disruption of the oocyte meiotic spindle or nuclear decondensation of spermatozoa (4).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on mouse models revealed that the chromosomal integrity of zygotes derived from ICSI without any pretreatment of spermatozoa was impaired in comparison with zygotes derived from conventional IVF [83]; even the culture sperm conditions may affect the chromosomal stability of the embryo [84]. Chromosomal damage may occur due to the injection of non-capacitated, acrosomeintact spermatozoa, so to reduce the risk of chromosomal aberrations during the ICSI procedure, it is crucial that sperm capacitation and the acrosome reaction be appropriately artificially induced in the proper medium before use [85].…”
Section: Intracytoplasmic Sperm Injection (Icsi) Technique and The Inmentioning
confidence: 99%